THE RELATIONSHIP BETWEEN NARCISSISM AND EMPLOYEE PERFORMANCE: STUDY ON CIVIL SERVANTS IN KUPANG CITY - Tuti Setyorini; Janri Manafe; Johan Adi (Jurnal Ekonomi, 2023)
The purpose of this study was to find out how the influence of narcissistic personality on employee performance. To achieve the purpose of the study, data will be collected through questionnaires that will be distributed to civil servants in Kupang City. This population was chosen because the performance of civil servants is often highlighted and considered to be still improvable. Previous studies have noted that excessive use of the internet and social media can lead to mental exhaustion of a person, and in terms of work, can decrease the person's performance. This study aims to highlight the personality of employees, in this case narcissism, which can affect the performance of civil servants. The results of this study show that narcissism can negatively affect an employee's performance.